2015
DOI: 10.5812/hepatmon.15(6)2015.28836
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pegylated Interferon Alpha and Ribavirin Efficacy and Long-Term Assessment of Relapse in Patients With Chronic Hepatitis C: A One-Center Experience From China

Abstract: Background:Sustained virological response (SVR) and virological relapse maintain pivotal roles in the management of chronic hepatitis C (CHC); however, there is little data regarding the long-term outcomes of patients with CHC in China.Objectives:We aimed to investigate the predictive factors of therapeutic effect and viral relapse in patients who achieved end-of-treatment response (ETR).Patients and Methods:We retrospectively analyzed clinical, biochemical and virological data of 169 adult patients with CHC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Since host genetic polymorphisms near the interferon-λ-3 (IFNL3, formerly known as IL28B) gene was recognized to be strongly associated with response to PEG-IFN/RBV therapy for chronic HCV, several clinical trials have revealed a prediction of treatment outcome by genotyping for the IL28B SNP ( 30 - 32 ). One of our previous studies also found that rates of SVR was significantly higher, and nonresponse and relapse rates were significantly lower in patients, who carried the favorable IFNL3 genotype (C/C for rs12979860) compared to the adverse IFNL3 genotypes (C/T and T/T) ( 33 ). However, the exact mechanisms behind this association were still only partially understood, and GWAS of IFNL3 SNPs were not reported to be functional.…”
Section: Discussionmentioning
confidence: 72%
“…Since host genetic polymorphisms near the interferon-λ-3 (IFNL3, formerly known as IL28B) gene was recognized to be strongly associated with response to PEG-IFN/RBV therapy for chronic HCV, several clinical trials have revealed a prediction of treatment outcome by genotyping for the IL28B SNP ( 30 - 32 ). One of our previous studies also found that rates of SVR was significantly higher, and nonresponse and relapse rates were significantly lower in patients, who carried the favorable IFNL3 genotype (C/C for rs12979860) compared to the adverse IFNL3 genotypes (C/T and T/T) ( 33 ). However, the exact mechanisms behind this association were still only partially understood, and GWAS of IFNL3 SNPs were not reported to be functional.…”
Section: Discussionmentioning
confidence: 72%
“…EVR defined as undetectable viral RNA 12 weeks after treatment has been described as a strong predictor of achieving SVR [27][28][29] in patients infected with HCV genotype 3a. 30 Monitoring ontreatment viral response has been shown useful in individualizing therapy with a high chance to cure and to prevent therapy from being unnecessarily prolonged. 31 Most of the studies reporting EVR as a predictor of SVR have been done in western countries with focus on genotype 1 infections.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that several factors influence the achievement of sustained virological response, such as: age, mode of virus transmission, genotype, severity of inflammatory changes in the liver, BMI and evidence of glucose abnormalities, actually insulin resistance. There are a number of studies that have made the analysis of a factors associated with SVR, highlighting the predictors of sustained virological response [16,17].…”
Section: Discussionmentioning
confidence: 99%